General anaesthesia in the dental management of a child with cerebral palsy and autism: A Case Report - Pradopo, Seno; Khairani, Firli Cahaya; Sudarsono, Wahyudi; Masyithah, Masyithah; Tedjosasongko, Udijanto (Faculty of Dental Medicine Universitas Airlangga, 2018)
Background: Cerebral palsy described as a spectrum of movement and posture disorders which result from pathological injury to the developing fetal or infant brain. Many conditions associated with cerebral palsy require surgery. Purpose: This article presents case report of a 15-year old, autistic male patient with cerebral palsy who required urgent management of multiple gangren radix, multiple pulpitis and gingivitis. Case Management: General anaesthesia was chosen for the purpose of behaviour management. The dental procedure were restoration with flow able composite of 7 teeth, extraction of 15 gangren radix, scaling of maxilla and mandibular region, also preventive treatment with topical aplication of fluoride. Discussion: Principles to the care of a such patient including early recognition, parental support, multi-disciplinary planning of procedure requiring general anesthesia, continuity of anesthesia care, and clear guidelines about the perioperative management of uncooperative children. Dental surgery under general anaesthesia was done, the patient was received restoration with flow able composite of 7 teeth, extraction of 15 gangren radix, scaling calculus at maxilla and mandibular region, also preventive treatment with topical aplication of fluoride. Conclusion: The case report showed that dental treatment should be done in patient with cerebral palsy and autism comprehensively.